The use of communication skills in teaching computer science and information technology as a socio-pedagogical problem. (Texas Journal of Multidisciplinary Studies, 2022)
Training, education and development of the new generation is carried out in an informationrich environment. Information technologies dictate new requirements for the professional and pedagogical qualities of a teacher, for the methodological and organizational aspects of using information and communication technologies in teaching. Today, any teacher has at his disposal numerous opportunities for using ICT tools in the learning process - this is information from the Internet, electronic textbooks, dictionaries and reference books, presentations, programs, various types of communication - chats, forums, blogs, e-mail, teleconferences, webinars and much more. The following article is devoted to the use of communication skills in teaching computer science and information technology as a socio-pedagogical problem.